2013
DOI: 10.2147/dnnd.s45980
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge among physical education professionals about poliomyelitis and post-poliomyelitis syndrome: a cross-sectional study in Brazil

Abstract: Background Post-poliomyelitis syndrome is a clinical condition that can affect poliomyelitis survivors with the onset of new symptoms several years after the acute disease. These symptoms include new muscular weakness, fatigue, pain, onset or aggravation of muscle atrophy, muscle cramps, onset or aggravation of pre-existing difficulties in accomplishing daily life activities, cold intolerance, sleep disorders, dysphonia or dysphagia, and respiratory deficiency. The treatment of post-poliomyelitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In particular, health professionals should be responsible for providing care/management to patients with different types of health intervention (prescription of diet and physical activity and emotional/psychological support), in routine medical consultations, and during emergencies. To this end, our research group has previously demonstrated that there is poor understanding of neurological diseases (including epilepsy) among health professionals [4][5][6][7]. In a survey by Vancini et al [5], nutritionists, physical educators, and physiotherapists received lower scores on their epilepsy knowledge test than other health professionals (medical doctors, psychologists, and nurses), demonstrating that improvement in education about epilepsy and inclusion of formal programs for epilepsy education, especially for nonmedical professionals, are needed.…”
Section: To the Editormentioning
confidence: 98%
“…In particular, health professionals should be responsible for providing care/management to patients with different types of health intervention (prescription of diet and physical activity and emotional/psychological support), in routine medical consultations, and during emergencies. To this end, our research group has previously demonstrated that there is poor understanding of neurological diseases (including epilepsy) among health professionals [4][5][6][7]. In a survey by Vancini et al [5], nutritionists, physical educators, and physiotherapists received lower scores on their epilepsy knowledge test than other health professionals (medical doctors, psychologists, and nurses), demonstrating that improvement in education about epilepsy and inclusion of formal programs for epilepsy education, especially for nonmedical professionals, are needed.…”
Section: To the Editormentioning
confidence: 98%
“…Post-poliomyelitis syndrome (PPS) is the term used to describe a collection of signs and symptoms that may be experienced by persons afflicted by paralytic poliomyelitis after years of clinical and functional stability [5]. The signs and symptoms that characterize PPS are new muscle weakness, muscle fatigue, muscle atrophy, muscle and joint pain, sleep disturbances, intolerance to cold, respiratory and swallowing difficulties and a recent increase in body mass [2,[6][7][8]. It is a slowly progressive disease, usually insidious, of subacute onset, sometimes resulting in significant restrictions of activities associated with everyday life [7,[9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…As success in the treatment of any disease depends of knowledge that the health professional has about disease, the assessment of knowledge about poliomyelitis and PPS in health professionals is of great value. Previously, it was demonstrated that physical education professionals have misconceptions about poliomyelitis and PPS [8], therefore, it is reasonable to assume that other health professionals present similar misconceptions in regard to poliomyelitis and PPS. Furthermore, other studies showed that health professionals can present misconceptions about epilepsy [27,28], acquired immune deficiency syndrome (AIDS) [29], cancer [30], hypertension and diabetes [31].…”
Section: Introductionmentioning
confidence: 99%
“…PPS is characterized by a new increased muscle weakness, fatigue, muscle and joint pain, muscle cramps, cold intolerance, and severe lung problems 4 . Recently, we conducted a study that evaluated the knowledge about poliomyelitis and PPS among Brazilian physical education professionals 5 . The knowledge about poliomyelitis and PPS were found to be low among these professionals, especially among those who had not access to previous information about PPS 5 .…”
mentioning
confidence: 99%
“…Recently, we conducted a study that evaluated the knowledge about poliomyelitis and PPS among Brazilian physical education professionals 5 . The knowledge about poliomyelitis and PPS were found to be low among these professionals, especially among those who had not access to previous information about PPS 5 . This situation could compromise the service provided, the services provided by these professionals.…”
mentioning
confidence: 99%